Thermosensory behaviors of the free-living life stages of Strongyloides species support parasitism in tropical environments. - Ben T Gregory; Mariam Desouky; Jaidyn Slaughter; Elissa A Hallem; Astra S Bryant (PLoS Neglected Tropical Diseases)
Soil-transmitted parasitic nematodes infect over 1 billion people worldwide and are a common source of neglected disease. Strongyloides stercoralis is a potentially fatal skin-penetrating human parasite that is endemic to tropical and subtropical regions around the world. The complex life cycle of Strongyloides species is unique among human-parasitic nematodes in that it includes a single free-living generation featuring soil-dwelling, bacterivorous adults whose progeny all develop into infective larvae. The sensory behaviors that enable free-living Strongyloides adults to navigate and survive soil environments are unknown. S. stercoralis infective larvae display parasite-specific sensory-driven behaviors, including robust attraction to mammalian body heat. In contrast, the free-living model nematode Caenorhabditis elegans displays thermosensory behaviors that guide adult worms to stay within a physiologically permissive range of environmental temperatures. Do S. stercoralis and C. elegans free-living adults, which experience similar environmental stressors, display common thermal preferences? Here, we characterize the thermosensory behaviors of the free-living adults of S. stercoralis as well as those of the closely related rat parasite, Strongyloides ratti. We find that Strongyloides free-living adults are exclusively attracted to near-tropical temperatures, despite their inability to infect mammalian hosts. We further show that lifespan is shorter at higher temperatures for free-living Strongyloides adults, similar to the effect of temperature on C. elegans lifespan. However, we also find that the reproductive potential of the free-living life stage is enhanced at warmer temperatures, particularly for S. stercoralis. Together, our results reveal a novel role for thermotaxis to maximize the infectious capacity of obligate parasites and provide insight into the biological adaptations that may contribute to their endemicity in tropical climates.